EVALUASI DAN PERANCANGAN PERBAIKAN JPO BERDASARKAN PERILAKU MENYEBERANG PEJALAN KAKI - Brillianti, Alfanisqi
In Indonesia, over half of pedestrian accidents are caused by jaywalking. Pedestrian safety should be given the highest priority among other road users. Even so, pedestrians must also fulfill their obligations by using the crossing facilities provided, such as pedestrian footbridge. The behavior of pedestrians who cross carelessly even though there is a footbridge is a problem that must be resolved. Therefore, the purpose of this study is to evaluate pedestrian intention to use a footbridge and design improvements to increase the intention of using it.